(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
Contemporary societies are currently subjected to very rapid and radical social changes and, as a consequence, struggle with their outcomes. The results range from the unforeseen repercussions of globally shifting political powers, through rising nationalisms, to prolonged economic, environmental, political and humanitarian crises. Critical analysis of the theories focused on the phenomena of authoritarianism, escapism, political myth, and conformity allows for outlining a comprehensive picture of the universally recognized opposition between freedom and security. From the distinction between the positive and negative freedom to the ambiguity surrounding the concept of “freedom from fear”, the fundamental dilemma is viewed from a historical perspective and illustrated with modern examples, emphasizing its current validity, insightfulness and potential in analyzing contemporary global problems. This approach allows for in-depth analyses of diversified social and political issues, such as the North African-European refugee crisis, rising nationalisms in the Western world, or a marked shift in political and social perspectives worldwide, from modern escapism to the birth of new myths of state.